Regulating Untaxable Externalities: Are Vehicle Air Pollution Standards Effective and Efficient? - Mark R. Jacobsen; James M. Sallee; Joseph S. Shapiro; Arthur A. van Benthem (Center for Economic Studies and ifo Institute (CESifo), 2022)
What is a feasible and efficient policy to regulate air pollution from vehicles? A Pigouvian tax is technologically infeasible. Most countries instead rely on exhaust standards that limit air pollution emissions per mile for new vehicles. We assess the effectiveness and efficiency of these standards, which are the centerpiece of US Clean Air Act regulation of transportation, and counterfactual policies. We show that the air pollution emissions per mile of new US vehicles has fallen spectacularly, by over 99 percent, since standards began in 1967. Several research designs with a half century of data suggest that exhaust standards have caused most of this decline. Yet exhaust standards are not cost-effective in part because they fail to encourage scrap of older vehicles, which account for the majority of emissions. To study counterfactual policies, we develop an analytical and a quantitative model of the vehicle fleet. Analysis of these models suggests that tighter exhaust standards increase social welfare and that increasing registration fees on dirty vehicles yields even larger gains by accelerating scrap, though both reforms have complex effects on inequality.
Keywords: H21; H23; H70; Q50; R40; 330; Luftverschmutzung; Kraftfahrzeug; Umweltstandard; Umweltabgabe; Regulierung; Internalisierung externer Effekte; USA